Prosthetic approach following traumatic evisceration: a case report - Mariska Juanita; Riezky Ramdhani; Irfan Dammar (Indonesian Journal of Prosthodontic, 2022)
A 20-year-old male patient was referred to Prosthodontic Department, Dental Hospital of Hasanuddin University, Makassar with chief complaint of disfiguration of the face. Medical history revealed a significant trauma to the left eye 6 months prior which stayed after evisceration. Patient has never used prosthetic eye afterwards. Examination of the left eye socket revealed a healthy conjunctiva covering the posterior wall of the anophthalmic socket with syn-chronous motions and absence of infection or inflammation signs. Sulcus depth was sufficient enough to retain prosthetic eye. This article presents rehabilitation of the ocular defect with customized acrylic-based ocular prosthe-sis to increase patient’s appearance and to prevent further shrinkage of the eye socket. Preliminary impression was done using customized tray fabricated from modelling wax and hydrocolloid irreversible impression material. An in-traocular custom tray for secondary impression was fabricated with acrylic resin and modified with a syringe that at-tached to the custom tray. Secondary impression of the defect was recorded using polyvinyl siloxane light viscosi-ty material followed by wax pattern fabrication using modelling wax. The wax pattern was tried in patient’s socket and checked for size, comfort, support, fullness, and then packed with tooth colored heat cure acrylic resin. After deter-mining the location and diameter of the iris with an optical vernier pupillary distance ruler, the color of sclera was de-termined by shade guide and confirmed with technician using digital photo. Ocular prosthesis was fabricated after-wards and inserted into the eye socket and evaluated for suitability, aesthetic and also movements with the contra-lateral eye. It is concluded that customized ocular prosthesis was significantly more aesthetic than pre-fabricated one with better contouring, color matching, and coordinated movements with the contralateral eye. This prosthetic ap-proach may restore patient’s appearance, increase their self-esteem, and improve their quality of life.